Tajweed Learning Education and Al-Qur'an Reading Assistance with the Ummi Method for 'Aisyiyah Jiken Branch Mothers - Supriyadi, Supriyadi; Rahmadhani, Gurit; Pramesta, Novi Indah; Zulfa, Nabila Indana (Indonesian Journal of Cultural and Community Development, 2025)
This community service activity aims to improve the ability of Aisyiyah mothers at the Al-Jihad Jiken Tulangan mosque to read the Qur'an correctly according to the rules of tajwid through the Ummi method with the Quran Explore method. The Ummi method was chosen because of its simplicity and effectiveness in teaching tajwid to adults. This activity was carried out through several stages, namely the introduction of the Ummi method, learning the theory of tajwid, application in reading the Qur'an, and group incentive assistance. The implementation of the activity was carried out in 4 meetings, with an evaluation carried out at the end of the program. The results obtained after the tajwid learning assistance program for the mothers of the 'Aisiyah Jiken branch leaders showed significant results, where students were able to read more fluently by understanding the basic science of tajwid. This assistance program succeeded in motivating students to continue learning and practicing independently. With this activity, it is hoped that it can be sustainable as a routine program to improve reading the Qur'an among the community.